LDL-C or apoB as the best target for reducing coronary heart disease: should apoB be implemented into clinical practice?. (February 2011) - Vaverkova, Helena
LDL-C is considered to be the major lipid risk factor and the main target of lipid-lowering therapy. Nevertheless, as all potentially atherogenic lipoprotein particles contain only one molecule of apoB and various amounts of cholesterol, apoB is a better marker of atherogenic particle numbers. Many laboratory, prospective and interventional studies have proven that apoB is a better indicator of cardiovascular risk than LDL-C. Statins lower LDL-C and non-HDL-C more (and to lower population percentile levels) than apoB. As a result, many patients treated with statins to achieve LDL-C and non-HDL-C targets remain at high risk owing to high levels of apoB, especially subjects with the prevalence of small dense LDL. With the worldwide increasing prevalence of obesity and metabolic syndrome, the issue of appropriate risk markers and treatment goals is even more important. On the basis of evidence from many studies, this article proposes that apoB should be included in guidelines as a part of the routine lipid panel. ApoB should be measured in all subjects with abnormal lipid profiles or high cardiovascular risk. Furthermore, apoB should be the primary target of lipid-altering therapy or, at least for the interim period of time, an additional goal. ApoB should be measured in all prospective and interventional studies to further support this suggestion and to optimize apoB targets. ApoB is also the promising target of LDL-lowering therapy. Therapeutic strategies directed at the hepatic assembly of VLDL (the precursor of LDL) should be explored in detail.